Habitat preference of Zoantharia genera depends on host sponge morphology - Alberto Acosta; Javier Montenegro-González (Universitas Scientiarum)
Studies about sponge-zoanthid symbioses have been focused on understanding the specificity of the association, rather thantesting what are the characteristics that make the host suitable to be colonized. For the first time it is investigated whether the ZoanthariaParazoanthus and Epizoanthus preference is related to the host sponge morphology (shape and mechanical resistance). Materials andmethods. Sponges were categorized according to their shape and mechanical resistance. The presence/absence of zoanthids was recordedin 1,068 sponges at San Andres Island, and their habitat preference was evaluated using indices and confidence intervals. Results. 85Parazoanthus colonies (78% of the total associations) and 24 Epizoanthus colonies (22%) were associated to sponges (10.2% in total).Parazoanthus uses branched and compressible sponges although prefers encrusting and fragile sponges, while Epizoanthus showes theopposite pattern, it can inhabit encrusting and fragile sponges but prefers branched and compressible sponges. Conclusion. These resultsindicated that sponge morphology is an important trait in zoanthid habitat selection. On the other hand, the similarity in the habitat used byzoanthids suggests the possibility of inter-generic competition if common resources are limited in time and space, while the differentialhabitat preference allows the competitive coexistence of both genera.